Dopamine modulation of transient receptor potential vanilloid type 1 (TRPV1) receptor in dorsal root ganglia neurons. (6th January 2016) - Chakraborty, Saikat; Rebecchi, Mario; Kaczocha, Martin; Puopolo, Michelino
Abstract : Key points: Transient receptor potential vanilloid type 1 (TRPV1) receptors transduce noxious thermal stimuli and are responsible for the thermal hyperalgesia associated with inflammatory pain. A large population of dorsal root ganglia (DRG) neurons, including the C low threshold mechanoreceptors (C‐LTMRs), express tyrosine hydroxylase, and probably release dopamine. We found that dopamine and SKF 81297 (an agonist at D1/D5 receptors), but not quinpirole (an agonist at D2 receptors), downregulate the activity of TRPV1 channels in DRG neurons. The inhibitory effect of SKF 81297 on TRPV1 channels was strongly dependent on external calcium and preferentially linked to calcium–calmodulin‐dependent protein kinase II (CaMKII). We suggest that modulation of TRPV1 channels by dopamine in nociceptive neurons may represent a way for dopamine to modulate incoming noxious stimuli. Abstract: The transient receptor potential vanilloid type 1 (TRPV1) receptor plays a key role in the modulation of nociceptor excitability. To address whether dopamine can modulate the activity of TRPV1 channels in nociceptive neurons, the effects of dopamine and dopamine receptor agonists were tested on the capsaicin‐activated current recorded from acutely dissociated small diameter (<27 μm) dorsal root ganglia (DRG) neurons. Dopamine or SKF 81297 (an agonist at D1/D5 receptors), caused inhibition of both inward and outward currents by ∼60% and ∼48%, respectively. The effect of SKF 81297 was reversed by SCH 23390 (an antagonist at D1/D5 receptors), confirming that it was mediated by activation of D1/D5 dopamine receptors. In contrast, quinpirole (an agonist at D2 receptors) had no significant effect on the capsaicin‐activated current. Inhibition of the capsaicin‐activated current by SKF 81297 was mediated by G protein coupled receptors (GPCRs), and highly dependent on external calcium. The inhibitory effect of SKF 81297 on the capsaicin‐activated current was not affected when the protein kinase A (PKA) activity was blocked with H89, or when the protein kinase C (PKC) activity was blocked with bisindolylmaleimide II (BIM). In contrast, when the calcium–calmodulin‐dependent protein kinase II (CaMKII) was blocked with KN‐93, the inhibitory effect of SKF 81297 on the capsaicin‐activated current was greatly reduced, suggesting that activation of D1/D5 dopamine receptors may be preferentially linked to CaMKII activity. We suggest that modulation of TRPV1 channels by dopamine in nociceptive neurons may represent a way for dopamine to modulate incoming noxious stimuli. Key points: Transient receptor potential vanilloid type 1 (TRPV1) receptors transduce noxious thermal stimuli and are responsible for the thermal hyperalgesia associated with inflammatory pain. A large population of dorsal root ganglia (DRG) neurons, including the C low threshold mechanoreceptors (C‐LTMRs), express tyrosine hydroxylase, and probably release dopamine. We found that dopamine and SKF 81297 (an agonist at D1/D5 receptors), but not quinpirole (an agonist at D2 receptors), downregulate the activity of TRPV1 channels in DRG neurons. The inhibitory effect of SKF 81297 on TRPV1 channels was strongly dependent on external calcium and preferentially linked to calcium–calmodulin‐dependent protein kinase II (CaMKII). We suggest that modulation of TRPV1 channels by dopamine in nociceptive neurons may represent a way for dopamine to modulate incoming noxious stimuli.